A magyar-román-szlovák-ukrán határmenti kapcsolatok az Európai Unió határtérségeinek fényében - Horváth, Anna (Közép-Európai Közlemények, 2024)
The development of border regions has been an integral part of EU regional policy for decades. Border regions, particularly in Central and Eastern Europe, are typically peripheral areas with poor demographic and economic conditions, and one of the ways out of this situation could be to take advantage of cross-border cooperation. One of the first frameworks for this was the creation of Euroregions and, since the 1990s, the Interreg programmes, which offer opportunities for cooperation between border regions at three levels. In addition to the EU framework, Hungarian strategic documents also deal with border regions, and their analysis is also important for the formulation of long-term objectives. Overall, although Interreg projects are trying to respond to the problems of border regions, it may be important in the future to deepen partnerships and better involve partners.